THE STRATEGIC PLANNING OF IS/IT AT PT. LINTAS GROUP - Hendra Maya Topani (Bina Nusantara University, 2011)
The purpose of this study is to find the requirement of Information Systems and Information Technology (IS/IT) in the development of the construction of Base Transceiver Station tower (BTS). The methodology that is used is the method of Ward and Peppard. The relevant data were extracted from interviews with the management. Questionnaires were distributed to 16 respondents, and observation was made accordingly. The results of this study are in the form of the application portfolio recommendation, proposal of the IT Division enhancement and the action time of IS/IT. The planning of IS/IT is as a guiding framework for the development of future changes at PT. Lintas Group.Keywords: Information System, Technology Information, application portfolio, telecommunication.